Impact of exposure to sub lethal concentration of Monocrotophos on blood parameters, biochemical constituents and histology of major carp, Catla catla (Hamilton) - T.S, Saravanan; S, Boopathi; D, Ashok; C., Kaethick (Malaysian Journal of Science, 2010)
The major carp, Calla calla on sub lethal exposure to monocrotophos for 30 days revealed significant decrease in blood parameters like RBC, WBC & Hb. As a result of chronic exposure the organic constituents like total free sugars, cholesterol and protein of liver and muscle also decreased significantly. Remarkable histological changes have also been observed in liver and gill of experimental groups. The reason for the significant reduction in blood parameters, tissue organic constituents and the histopathological changes is discussed.